ANALISIS KESALAHAN PENGGUNAAN KALIMAT “BA” DAN “BEI” PADA MAHASISWA PRODI PENDIDIKAN BAHASA MANDARIN ANGKATAN 2019 FKIP UNTAN - Ashri Amalia Pandhita; Ina Ina; Yoanna Afrimonika (Universitas Tanjungpura, 2022)
In Mandarin, many words are used differently from other languages, some even doesn’t exist in other languages, one of which is the prepositions